An infrastructure master plan for developing Pulau Pangkor as a new eco-tourist destination - Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (2014)
The vision of Perak Amanjaya Development Plan is to enhance the socio-economic status of Perak people corresponding to the Federal Government’s development philosophy. In order to achieve this vision, Institut Darul Ridzuan is committed in playing the roles whereby IDR assists the Perak State Government in formulating development policies and initiating innovative strategies and programs with the aim of driving peace, stability and progress by focusing on the delivery of “3Qs” – Quality Opportunity, Quality Income and Quality Living. Therefore, collaboration with local and International research communities, helped IDR to gain insights into the theoretical and practical problems concerning the development in Perak State. One of the projects is to study the infrastructure and public utilities in Pulau Pangkor as vibrant tourism destination. To achieve the goal, the research is conducted regarding the infrastructure master plan for developing Pulau Pangkor as a new eco-tourism tourist destination.